2023
DOI: 10.1371/journal.pntd.0011490
|View full text |Cite
|
Sign up to set email alerts
|

Chagas disease is related to structural changes of the gut microbiota in adults with chronic infection (TRIPOBIOME Study)

Abstract: Background The implications of the gut microbial communities in the immune response against parasites and gut motility could explain the differences in clinical manifestations and treatment responses found in patients with chronic Chagas disease. Methodology/Principal findings In this pilot prospective cross-sectional study, we included 80 participants: 29 with indeterminate CD (ICD), 16 with cardiac CD (CCD), 15 with digestive CD (DCD), and 20 controls without CD. Stool was collected at the baseline visit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Early studies in germ-free mice showed worse disease outcomes than in conventional mice (for instance, [115]), however, with the caveat that such mice present with significant immune-maturation defects [116]. T. cruzi infection persistently perturbs the gut microbiome in mouse models [70,117,118] and in humans [119][120][121]. These changes were correlated with metabolic alterations, in particular in bile acids and fatty acids [70,117].…”
Section: Beyond Cross-eukaryote Interactions: Metabolic Role Of the M...mentioning
confidence: 99%
“…Early studies in germ-free mice showed worse disease outcomes than in conventional mice (for instance, [115]), however, with the caveat that such mice present with significant immune-maturation defects [116]. T. cruzi infection persistently perturbs the gut microbiome in mouse models [70,117,118] and in humans [119][120][121]. These changes were correlated with metabolic alterations, in particular in bile acids and fatty acids [70,117].…”
Section: Beyond Cross-eukaryote Interactions: Metabolic Role Of the M...mentioning
confidence: 99%